Parametric Optimization for Selective Surface Modification in EDM Using Taguchi Analysis. Issue 4 (11th March 2016) - Rahang, Maneswar; Patowari, Promod Kumar
Abstract : This paper introduces selective modification of surface by electric discharge machining process and its parametric optimization. A hard layer of tungsten and copper mixture is created at selected area of aluminum surface. The process is done using W–Cu powder metallurgical green compact tool and masking technique in die-sinking electric discharge machining (EDM). The modified surface is evaluated by the performance measures such as tool wear rate, material transfer rate, surface roughness, and edge deviation from the pre-defined boundary line of deposited layer by analysis of variance using Taguchi design of experiment. Minimum surface roughness of 4.5 µm and minimum edge deviation of 37.29 µm is achieved. The hardness of the surface layer is increased more than three times of base metal. Overall effects of parameters are also analyzed considering multiple performance criteria using overall evaluation criteria. The modified surface is characterized using scanning electron microscopy and energy dispersive spectroscopy analysis, which show the tool material transfer at the selected area of the surface.